2014
DOI: 10.1016/j.bjid.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A search for Clostridium difficile ribotypes 027 and 078 in Brazil

Abstract: Toxigenic strains of Clostridium difficile may be disseminating. Here we prospectively screened patients with nosocomial diarrhoea in two hospitals in Brazil. To identify C. difficile polymerase chain reaction ribotypes 027/078 strains, we used high resolution melting and multiplex polymerase chain reaction. Among 116 screened patients, 11 were positive for C. difficile. The polymerase chain reaction ribotypes 027/078 strains were not identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…However, typical clade 5 strains (RT078 and RT126) were detected in two patients (2.7%) but corresponded to more than 60% of the animal isolates in the present study. These results corroborate those of previous studies that failed to detect RT078 in humans in Brazil, whereas both RT078 and 126 have been already reported in several animal species, including swine, horses, and rodents [8,10,13,82,83]. This finding contrasts with reports in European countries and in North America, where RT078 seems to be common in both humans and animals [84,85].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…However, typical clade 5 strains (RT078 and RT126) were detected in two patients (2.7%) but corresponded to more than 60% of the animal isolates in the present study. These results corroborate those of previous studies that failed to detect RT078 in humans in Brazil, whereas both RT078 and 126 have been already reported in several animal species, including swine, horses, and rodents [8,10,13,82,83]. This finding contrasts with reports in European countries and in North America, where RT078 seems to be common in both humans and animals [84,85].…”
Section: Plos Onesupporting
confidence: 90%
“…Studies suggest that RT027 and RT078 are extremely rare in humans in Brazil [8][9][10]. The absence or rare isolation of both RT027 and RT078 contrasts with reports in North America and most European countries but is consistent with previous studies reported in China that have suggested the emergence of other potentially epidemic genotypes of C. difficile, including strains from clade 3 [11].…”
Section: Introductionsupporting
confidence: 85%
“…In Latin America, some CDI cases have documented and the NAP1/027 ribotype was reported in Costa Rica, Panama, México, Chile and Colombia [ 14 – 19 ]. Other ribotypes including 014, 106, 010, 020, 133 and 233 have been registered in Brazil, but 027/078 have not yet been detected [ 20 22 ]. Although, ribotye NAP1/027 has been reported in Colombia [ 23 ], the diversity of circulating genotypes remains to be described.…”
Section: Introductionmentioning
confidence: 99%